Homogenizer-intensified room temperature emollient ester isoamyl oleate production - Tarigan, Juliati Br; Santoso, Aman; Sitepu, Eko K.; Supeno, Minto; Peranginangin, Sabarmin; Sihotang, John P.; Tarigan, Gloria M.; Chaidir, David; Taufiq-Yap, Y. H. (Elsevier B.V., 2025)
The present study reports a successful experiment to produce emollient ester isoamyl oleate (IAO) in room temperature conditions. The process was conducted under mild conditions without external heating. A factorial design was applied to study the effects of molar ratio, catalyst concentration, and rotational speed over different reaction times. The highest IAO conversion (99.3 %) was achieved within just 5 min at room temperature using a 1: 3 M ratio, 0.1 M catalyst concentration, and 4000 rpm rotational speed. The reaction was completed rapidly due to enhanced mass transfer and mixing. Compared to conventional reflux and microwave-assisted methods, the homogenizer-assisted process reduced energy consumption by up to 93 % and reaction time by over 90 %. This approach demonstrates a promising green alternative for ester production with significant energy and time savings.